2017
DOI: 10.1111/ahg.12184
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Whole Exome Sequencing with Cardiometabolic Traits Using Family-Based Linkage and Association in the IRAS Family Study

Abstract: Summary Family-based methods are a potentially powerful tool to identify trait-defining genetic variants in extended families, particularly when used to complement conventional association analysis. We utilized two-point linkage analysis and single variant association analysis to evaluate whole exome sequencing (WES) data from 1,205 Hispanic Americans (78 families) from the Insulin Resistance Atherosclerosis Family Study. WES identified 211,612 variants above the minor allele frequency threshold of ≥0.005. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…All sequence reads passed through the Illumina Data Analysis Pipeline, and those from samples passing QC criteria were mapped to the human genome reference sequence (hg19). A detailed description of the sequencing platform and analysis pipeline has been published 36 . Of note, multi-sample recalibration was performed prior to variant calling.…”
Section: Methodsmentioning
confidence: 99%
“…All sequence reads passed through the Illumina Data Analysis Pipeline, and those from samples passing QC criteria were mapped to the human genome reference sequence (hg19). A detailed description of the sequencing platform and analysis pipeline has been published 36 . Of note, multi-sample recalibration was performed prior to variant calling.…”
Section: Methodsmentioning
confidence: 99%
“…A similar study in the same population identified a low‐frequency variant (rs2076349) in the laminin subunit beta 3 ( LAMB3 ) gene associated with morbid obesity and BMI . A whole‐exome single‐variant association analysis in 1,205 Hispanic Americans (78 families) identified a low‐frequency variant (rs11554137) in the isocitrate dehydrogenase 1 ( IDH1 ) gene associated with BMI at the conventional genome‐wide level of significance . WES in 177 Pima Indians followed by targeted genotyping in >13,000 additional subjects identified two common SNPs in the cytochrome b5 type A ( CYB5A ) and ring finger protein 10 ( RNF10 ) genes associated with body fatness, maximum recorded BMI in childhood and adulthood and T2D .…”
Section: Established Strategiesmentioning
confidence: 95%
“…Whole exome sequencing is a new powerful strategy to discover causative genes in rare Mendelian disorders 12 . Recently, this technology combined with a filtering methodology was demonstrated as an approach to identify susceptible genes among many genetic diseases 13 . Moreover, many genetic variants of common diseases such as diabetes, hypertension and tumor were found by this approach 14 16 .…”
Section: Introductionmentioning
confidence: 99%